1973
DOI: 10.1021/ja00804a019
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric liquid crystal induced circular dichroism (LCICD). V. Mechanistic aspects of LCICD

Abstract: 7656 Figure 4. Energy surface (one-electron contributions) of the butadiene-cyclobutene ground configuration as a function of independent rotational angles $ and $'. Dotted lines: $ = -$' conrotation, @ = +$' disrotation. (Note: @' = +90° is electronically equivalent to $' = -90" and the surface repeats periodically for angles outside the given range.) path in this molecular state lies on a smooth energy slope, with no intervening energy maximum between the two paths. (This is true on either side of the peak v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 1 publication
(1 reference statement)
4
51
0
2
Order By: Relevance
“…7) indicates that the phase (L a D ) has also helical arrangements like the Ch phase, but the degree of helical twist in the L a D phase is significantly lower (i.e., longer pitch) than in the Ch phase (35). If the L a D phase would be a twophase region consisting of Ch-and L a phases, it would have shown an LCICD band of intensity comparable to that observed in the Ch phase, because the LCICD intensity is almost independent of the concentration of the pyrene dissolved in the mesophase as it was put forward by Saeva et al (35).…”
Section: Phase Transformations Along the Line A (W S 30)mentioning
confidence: 99%
“…7) indicates that the phase (L a D ) has also helical arrangements like the Ch phase, but the degree of helical twist in the L a D phase is significantly lower (i.e., longer pitch) than in the Ch phase (35). If the L a D phase would be a twophase region consisting of Ch-and L a phases, it would have shown an LCICD band of intensity comparable to that observed in the Ch phase, because the LCICD intensity is almost independent of the concentration of the pyrene dissolved in the mesophase as it was put forward by Saeva et al (35).…”
Section: Phase Transformations Along the Line A (W S 30)mentioning
confidence: 99%
“…Therefore, the cholesteric liquid crystal structure is believed to be a good chiral template, which can precisely control the molecular orientation through intermolecular interactions. Many achiral dye molecules can be arranged helically in the cholesteric liquid crystals and show induced CD signals, [8][9][10][11][12][13][14] that is liquid crystal induced CD.DNA is a chiral molecule, which is used as a chiral template to induce many achiral dyes to show induced CD signals. [15][16][17][18][19][20][21] DNA aqueous solution can form cholesteric liquid crystal structure when the concentration is higher than the critical value 22 and can induce the chirality of achiral dye molecules, such as Ethidium bromide, Bisbenzimide, etc.…”
mentioning
confidence: 99%
“…Therefore, the cholesteric liquid crystal structure is believed to be a good chiral template, which can precisely control the molecular orientation through intermolecular interactions. Many achiral dye molecules can be arranged helically in the cholesteric liquid crystals and show induced CD signals, [8][9][10][11][12][13][14] that is liquid crystal induced CD.…”
mentioning
confidence: 99%
“…F) Pyrene£-CDx: 86 The band of pyrene at the longest wavelength is polarized along the long axis (Figure 45g). 84 Associated with this band, pyrene in £-CDx (2:1 complex, confirmed by Job's continuous variation experiments) shows a minus-to-plus CD pattern in ascending energy, so that it was confirmed that two pyrene molecules take the form of a left-handed conformer in the cavity of £-CD (Figure 45j). G) Charge-transfer complex formation in CDxs: 87 If we dissolve electron-deficient and -rich compounds in solution, they may form CT complexes.…”
Section: Circular Dichroism Of Cyclodextrinchromophore Systemsmentioning
confidence: 71%
“…D) Pyrenetetrasulfonate: 83 The polarization direction of the absorption bands of pyrene had been well established as short as ca. 240 nm 84 and by us up to ca. 200 nm using the ¢-CDxpyrene system (Figure 45g).…”
Section: Circular Dichroism Of Cyclodextrinchromophore Systemsmentioning
confidence: 76%